Penggunaan Media Sosial Tiktok Sebagai Sarana Informasi Politik Generasi Z - Sari, Qurratul Ain Adinda; Candrasari, Yuli (Jurnal Ilmiah Wahana Pendidikan, 2023)
Social media is currently developing, especially on social media Tiktok which is associated with some content and information about politics or related political events that can provide some understanding for generation Z regarding political developments in Indonesia. This is based on research conducted on this matter, namely using Tiktok social media as a means of political information for generation Z. So this research has the goal of providing an overview of the role of Tiktok as a means of political information for generation Z. The data collection technique for this research was carried out through a literature review and several literature studies adapted to the research. The results of the study make it clear that Tiktok, which is used to communicate political information, can influence Gen Z. This can be seen from a survey conducted for 48 hours on June 25-26 2023 using the Google Form application which managed to collect data from 99 respondents from generation Z who live in Surabaya City. This data analysis was carried out descriptively by looking at the percentage of respondents who already answered on the questionnaire.